PENERAPAN METODE SOSIODRAMA DENGAN MEDIA VISUAL UNTUK MENINGKATKAN PEMBELAJARAN IPS TENTANG PERANAN TOKOH DALAM MEMPROKLAMASIKAN KEMERDEKAAN PADA SISWA KELAS V SDN 4 KUTOSARI TAHUN AJARAN 2015/2016 - PERTIWI, HERLIN REZZA (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Sociodrama Method Using Visual Media in Improving Social Science Learning about the Roles of Notable Figures in Indonesian Independence for the Fifth Grade Students of SD Negeri 4 Kutosari in the Academic Year of 2015/2016. The objective of this research is to improve social science learning for the fifth grade students of SD Negeri 4 Kutosari, This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of two meetings including planning, action, observation, and reflection. Subjects of the research were fifth grade students of SD Negeri 4 Kutosari in academic year of 2015/2016 totaling 29 students. Techniques of collecting data were test, observation, interview, and documentation. The results of this research showed that the application of sociodrama method using visual media can improve social science learning fot the fifth grade students of SD Negeri 4 Kutosari in academic year of 2015/2016. Keywords: Sociodrama, visual, social science Abstrak: Penerapan Metode Sosiodrama dengan Media Visual untuk Meningkatkan Pembelajaran IPS tentang Peranan Tokoh dalam Memproklamasikan Kemerdekaan pada Siswa Kelas V SDN 4 Kutosari Tahun Ajaran 2015/2016. Penelitian ini bertujuan untuk meningkatkan pembelajaran IPS siswa kelas V SDN 4 Kutosari. Penelitian ini merupakan penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus terdiri dari tahap perencanaan, pelaksanaan, pengamatan dan refleksi. Subjek penelitiannya adalah siswa kelas V SDN 4 Kutosari yang berjumlah 29 siswa. Teknik pengumpulan data dalam penelitian ini menggunakan tes, observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan penerapan metode sosiodrama dengan media visual dapat meningkatkan pembelajaran IPS siswa kelas V SDN 4 Kutosari Tahun Ajaran 2015/2016. Kata Kunci: Metode Sosiodrama, media visual, IPS